Foot-and-mouth disease virus (FMDV) with a stable FLAG epitope in the VP1 G-H loop as a new tool for studying FMDV pathogenesis. - Lawrence, P; Pacheco, J; Uddowla, S; Hollister, J; Kotecha, A; Fry, E; Rieder, E (2013)
Foot-and-mouth disease virus (FMDV) VP1 G-H loop contains the major antigenic site. By replacing the sequence upstream of the RGD motif with a FLAG epitope, a marker virus for pathogenesis studies was generated. In cell culture, the recombinant virus containing FLAG (A24-FLAG) exhibited similar plaque phenotypes and growth kinetics to parental virus. A24-FLAG was distinguished, neutralized, and immunoprecipitated by FLAG anti-sera. A24-FLAG infected cattle exhibited FMD and an antibody response similar to parental virus. FLAG epitope stability was confirmed both in vitro and in vivo. Interestingly, no anti-FLAG antibodies were detectable in cattle up to 21 days post-inoculation. A24-FLAG G-H loop modeling suggested FLAG was rendered a cryptic site, inaccessible to the host immune system. These studies demonstrate the FMDV VP1 G-H loop tolerance to substitutions without detriment to pathogenesis and antigenicity. Finally, A24-FLAG manifested virulence in cattle as parental virus, and could be distinguished and tracked by tag-specific anti-sera.